Brain–Immune Interactions and Neuroinflammation After Traumatic Brain Injury - Dinet, Virginie; Petry, Klaus G.; Badaut, Jerome (Frontiers in Neuroscience, 2019)
Traumatic brain injury (TBI) is the leading cause of death and disability in children and young adults. Tremendous clinical and pre-clinical efforts have been undertaken to understand the acute, life threatening pathophysiological events occurring after severe TBI. In the past few years, however, it was recognized that TBI causes significant morbidity weeks, months or even years after the initial event, thereby contributing substantially to the overall burden of TBI and the decrease of life expectancy in these patients. Long-lasting sequels of TBI include cognitive decline/dementia, sensory-motor dysfunction, psychiatric disorders and most important for patients is the need in socio-economic rehabilitation affecting their quality of life. Cerebrovascular alterations have been described during the first week after TBI with for direct consequence development of neuroinflammatory process in relation with brain edema. Within the brain-immune interactions the complement system, which is a family of blood and cell surface proteins, is participating in the pathophysiology process. In fact, the complement system is part of primary defense and clearance component of innate and adaptive immune response. In this review, the complement activation after TBI will be described in relation with the activation of the microglia and astrocytes as well as the blood-brain barrier dysfunction during the first week after the injury. Considering the neuro-inflammatory activity as causal element of the neurological handicaps, some major parallel lines of complement activity in Multiple sclerosis and Alzheimer pathologies with regard to cognitive impairment will be discussed for chronic TBI. A better understanding of the role of complement activation could facilitate the development of new therapeutic approaches for TBI.